(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Uterine rupture is a rare complication that can occur in the first trimester of pregnancy. It can lead to serious maternal morbidity or mortality, mostly because of catastrophic bleeding. First-trimester uterine rupture is rare; hence, diagnosis can be challenging as it may be confused with other causes of early pregnancy bleeding, such as an ectopic pregnancy. We present a case of first-trimester scar dehiscence and conduct a literature review of this rare condition. Case presentation: A 39-year-old patient with 4 previous hysterotomy scars presented with severe lower abdominal pain at 11 weeks of gestation. The patient had two previous histories of third-trimester uterine rupture in previous pregnancies with subsequent hysterotomy and repair. The patient underwent a diagnostic laparoscopy that confirmed the diagnosis of a 10 cm anterior wall uterine rupture. A laparotomy and repair of the rupture was subsequently performed. Conclusion: This case presented adds to the body of evidence of uterine scar dehiscence in the first trimester. The outline risk factors, clinical presentation, diagnostic imaging, and management may help in the early identification and management of this rare but life-threatening condition.